2007
DOI: 10.1007/s11517-007-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation of a protein–water system in atherosclerotic artery wall

Abstract: Measurements of the dielectric properties of healthy and atherosclerotic human artery tissues were made in the frequency range of 100 Hz-100 kHz and temperatures from 22 to 260 degrees C. The temperature dependencies of the dielectric parameters for healthy tissues reveal distinctively the temperature ranges corresponding to the release of water up to 200 degrees C and the decomposition processes of elastin and collagen, above this temperature. The influence of atherosclerosis on the dielectric properties of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…2 and 3(a and b) show the effect of frequency on the dielectric behavior of the diabetic and the healthy nail previously kept at 120 and 200°C, respectively. For the air-dried nail (not presented) the frequency only affects the amplitude but not the temperature of the e 0 and e 00 peaks, similarly as for wet horn [20] and other tissues [16,21]. The peaks in e 00 of the b-relaxation for both samples are shifted to lower temperatures as the frequency decreases.…”
Section: Methodsmentioning
confidence: 82%
“…2 and 3(a and b) show the effect of frequency on the dielectric behavior of the diabetic and the healthy nail previously kept at 120 and 200°C, respectively. For the air-dried nail (not presented) the frequency only affects the amplitude but not the temperature of the e 0 and e 00 peaks, similarly as for wet horn [20] and other tissues [16,21]. The peaks in e 00 of the b-relaxation for both samples are shifted to lower temperatures as the frequency decreases.…”
Section: Methodsmentioning
confidence: 82%
“…Organ physical damage (e.g., cell deformation) can be seen based on a decrease in the value of the dielectric constant [33,34]. The dielectric constant can be used to indicate the nature or characteristics of a material.…”
Section: Discussionmentioning
confidence: 99%
“…Although the predictive role of inflammatory markers in advanced coronary artery disease has been proven [19,20], the pathophysiological basis of the relationship between inflammatory activation and coronary atherosclerosis has not been investigated. Brzezinski et al suggested physicochemical changes measured by dielectric spectroscopy in collagen in comparison to elastin related to peripheral artery disease [21].…”
Section: Introductionmentioning
confidence: 99%